2014
DOI: 10.1111/1462-2920.12618
|View full text |Cite
|
Sign up to set email alerts
|

System‐wide characterization of bZIP transcription factor proteins involved in infection‐related morphogenesis of Magnaporthe oryzae

Abstract: The basic-leucine zipper (bZIP) domain-containing transcription factors (TFs) function as key regulators of cellular growth and differentiation in eukaryotic organisms including fungi. We have previously identified MoAp1 and MoAtf1 as bZIP TFs in Magnaporthe oryzae and demonstrated that they regulate the oxidative stress response and are critical in conidiogenesis and pathogenicity. Studies of bZIP proteins could provide a novel strategy for controlling rice blast, but a systematic examination of the bZIP prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 72 publications
0
102
0
1
Order By: Relevance
“…S3C and D). We further examined the expression of genes essential for conidiation and found that the expression of MoCOM1 , MoHOX2 , MoCOS1 and MoSTUA were all reduced in the Δ Moppe1 mutant when compared with the wild‐type strain (Kim et al ., ; Nishimura et al ., ; Zhou et al ., ; Yang et al ., ; Tang et al ., ) (Supporting Information Fig. S4).…”
Section: Resultsmentioning
confidence: 99%
“…S3C and D). We further examined the expression of genes essential for conidiation and found that the expression of MoCOM1 , MoHOX2 , MoCOS1 and MoSTUA were all reduced in the Δ Moppe1 mutant when compared with the wild‐type strain (Kim et al ., ; Nishimura et al ., ; Zhou et al ., ; Yang et al ., ; Tang et al ., ) (Supporting Information Fig. S4).…”
Section: Resultsmentioning
confidence: 99%
“…By using DTT as an ER stress inducer, we demonstrated that MoGlo3 has a role in the ER stress response. In addition, we showed that MoGlo3 has a role in the UPR pathway mediated by MoHac1 and MoMck1 (Tang et al ., ; Yin et al ., ). Since ER stress is hypothesized to occur during infection and invasive hyphae growth and that the fully functional UPR is required for penetration and invasive hyphae growth (Tang et al ., ), the perturbed UPR pathway under ER stress in the Δ Moglo3 mutant might foretell a defect in pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…2). The bZIP TFs represent one of the largest TF families among the eukaryotes and may regulate a broad range of biological processes including hyphal growth, virulence in pathogenic fungi and responses to oxidative stress (Kong et al, 2015;Tang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%